2016
DOI: 10.1371/journal.pone.0154630
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Induces Antigen-Specific Tolerance in Experimental Collagen-Induced Arthritis

Abstract: Here, we investigate induction of immunological tolerance by lentiviral based gene therapy in a mouse model of rheumatoid arthritis, collagen II-induced arthritis (CIA). Targeting the expression of the collagen type II (CII) to antigen presenting cells (APCs) induced antigen-specific tolerance, where only 5% of the mice developed arthritis as compared with 95% of the control mice. In the CII-tolerized mice, the proportion of Tregs as well as mRNA expression of SOCS1 (suppressors of cytokine signaling 1) increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…A critical role for anti-CII specific IgG for the development of CIA has been demonstrated by previous studies 1 and it has been shown that the lgG2a subclass is a major produced antibody against CII. 36 In addition, some adoptive T cell therapy works shown a decrease in the levels of hallmarks CII-specific IgG 14 and IgG2a.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A critical role for anti-CII specific IgG for the development of CIA has been demonstrated by previous studies 1 and it has been shown that the lgG2a subclass is a major produced antibody against CII. 36 In addition, some adoptive T cell therapy works shown a decrease in the levels of hallmarks CII-specific IgG 14 and IgG2a.…”
Section: Discussionmentioning
confidence: 77%
“…Rheumatoid arthritis (RA) is a chronic inflammatory joint disease 1 which is characterized by proliferative synovitis of diarthrodial joints that leads to articular cartilage and bone destruction 2 RA is widely believed to be an autoimmune disorder where dysregulation of self-tolerance mechanisms leads to generation of auto reactive lymphocytes which target tissue-specific auto antigens derived from joint. 3 Similar to most autoimmune disorders, exact tissuespecific self-antigens and also precise pathogenic events leading to RA are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Presentation of the immunodominant T-cell epitope in CII, the CII-peptide amino acids 259–270, on MHC II A q is important for both disease development [ 23 , 24 ] and tolerance [ 16 , 17 , 25 ]. We have shown previously that adoptive transfer of B cells presenting the CII - peptide on MHC II A q induces partial tolerance to CIA [ 19 ]. In these experiments we used the LNT-SFFV-CII/CLIP lentiviral vectors, where expression of CII was driven by the general SFFV promoter (Additional file 3 : Figure S3B).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that administration of lentiviral particles which results in expression of the CII-peptide on all APCs induces tolerance [ 17 19 ]. Here, we use our lentiviral system to target expression of the CII-peptide specifically on B cells, using a B-cell specific Igk promoter [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Background RA treatment usually consists of combined therapies that suppress the entire immune response, leading to increased susceptibility to a plethora of infections. In this sense, many efforts are made to develop more specific immunomodulatory strategies as, for example, the induction of antigen-specific tolerance [86][87][88]. Self-tolerance can be induced by different procedures such as self-antigen administration via tolerogenic routes (oral mucosa, for example), concomitant blocking of co-stimulatory molecules, or self-antigen targeting to resting antigen-presenting cells, such as DCs [89].…”
Section: Tolerogenic Effect Of Vitamin D In Experimental Arthritismentioning
confidence: 99%